Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Veneria4

  • 4 years ago

if the solution of (x+1)(3x^2-2x-1)=0 then x+1/x= ?

  • This Question is Closed
  1. pk51
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    x = -1, -1/3, 1

  2. dinainjune
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    (x+1) (3x+1) (x-1) = 0 x+1=0 x=-1 sub to x+1/ x =0/-1 = 0 3x+1=0 x=-1/3 sub to x+1/ x = (2/3) / (-1/3) = -2 x-1 =0 x=1 sub to x+1/ x = 2/1 = 2

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy